Decolonising and Africanising the Further Education And Training (FET) history curriculum in South Africa (Grades 10-12): integration of heritage sites and institutions of memory in the Western and Eastern Cape - Phunguza, Sibongiseni (ASL: African Studies and Linguistics, 2026)
The politics of heritage have progressively played a critical role in South African socio-political life since 1994. As an example, heritage institutions have played a major role in re-centring histories that were pushed to the periphery within the decolonisation discourse in post-Apartheid South Africa. Heritage has therefore also been seriously considered in the decolonisation of education in South Africa, especially in teaching History as a subject. This thesis critically analyses the integration of heritage sites and institutions of memory into the FET (grades 10-12) history curriculum, and how this integrated process of knowledge production could contribute towards building an Africa-centric curriculum. It argues that by centering African heritage sites and institutions of memory in knowledge production and education, the FET history curriculum can be radically decolonised and shifted towards indigenous knowledge prioritisation. The thesis explores two aspects in this argument: (1) How could we integrate heritage sites and institutions of memory into the FET history curriculum and (2) how could we teach topics that are covered in the curriculum by using African-informed foundations of research and knowledge production. The thesis argues that these two processes are interdependent and intersectional in nature.